Association between Variant Alleles of the X-Ray Cross Complementing Gene (XRCC1) with Benzo[a]Pyrene Levels in Iraqi Workers - R. Omrain, Alaa; A.R. Al-Wasiti, Estabraq; Jassim Hamzah, Mohammed (Journal of Contemporary Medical Sciences, 2022)
Objectives: Assessment of a single nucleotide polymorphism of the XRCC1 (codon Arg399Gln) gene and its association with levels of benzo[a]pyrene in blood of car repairers and control group. Methods: The current study included (111) participants, (37) of the iraqi car repairers, (37) sellers of spare part, and (37) healthy (controll), with the same age range. benzo[a]pyrene was determined by using HPLC technique. Alleles frequency of singl nucleotide polymorphisms of XRCC1 gene was determined by Restriction fragment length polymorphisms (PCR-RFLP). Results: The results of current study indicated that there is a highly significant increase of B[a]P level (p= 0.0001) in the repairers group compared to the groups of spare part sellers and control together. The genotype frequencies studies of XRCC1 gene of car repairers group and controls. The effect of rs25487 genotypes on exposure to PAHs include higher levels of PAHs and PAH-DNA adduct in TT genotype followed by CT genotype and CC showed lower levels. Conclusions: As results of prolonged exposure to the higher levels of PAHs that Iraqi car repaiers suffer from, they have highe levels B[a]P. especially those who have the TT genotypes, as results of the inefficiency of thier DNA repair system. Compared to the other genotypes.